Familiarity, challenge, and processing of persuasion messages - Garcia-Marques, Teresa (2015)
This article focuses on how familiarity moderates task engagement. Blascovich et al. (1993) have demonstrated that task familiarity generally evokes challenge motivation; that is, the experience of having sufficient resources to meet task demands. Garcia-Marques, Mackie, Claypool, and GarciaMarques (2013) have demonstrated that individuals attend less to details while performing familiar tasks thereby processing information more superficially. The relationship between these two effects was tested in two experiments including the assessment of both the physiological measures that index individuals’ motivational states and of the way in which individuals process information. Experiment 1 revealed that familiarity with a persuasive message independently activates both a physiological challenge response and reduces participants’ sensitivity to argument quality. Experiment 2 provided additional evidence that the two effects act independently by showing that social presence moderates the first effect but not the second.